205 IMMERSIVE HIGH-FIDELITY SIMULATOR-BASED TEACHING FOR ANESTHESIOLOGY NURSING STUDENTS RESULTS IN STEADY PERFORMANCE PATTERNS IN TRAINEES. (1st January 2006) - Kozmenko, V.; Morgan, B.; Kaye, A.; Wren, K.; Hilton, C.
Abstract : Purpose: The purpose of this project was to develop an immersive high-fidelity simulator-based, context-specific course for training anesthesia nursing students to effectively function in the stressful operating room (OR) environment. Methods: Teaching sessions occurred in a fully equipped virtual OR. We used a student-focused high-fidelity simulator-based method of teaching based on the principles of adult learning. The following interactive scenarios comprised the course: simple intravenous induction into anesthesia, thermal injury with smoke inhalation, multiple trauma with tension pneumothorax and internal bleeding, intraoperative wheezing due to bronchial asthma exacerbation, intraoperative anaphylactic reaction, malignant hypothermia, and intraoperative septic shock. Students' critical thinking and clinical interventions determined the outcomes of the cases. To produce steady changes in clinical behaviors, we exposed the students to each case multiple times slightly modifying the patients' profiles. The students perceived each case as a new one. We assessed performance by direct observation and filling out case-specific assessment forms. The students worked on cases in random order as many times as was needed to develop steady clinical behavioral patterns that reflected best clinical practices. We followed each session with a guided debriefing during which the students reflected on their performances. Results: As the course progressed, we observed several phenomena in students' behavior: developing of suspension of disbelief during the sessions, more objective assessment of personal skills and knowledge, more effective management of the OR stress, more efficient disintegrating complex problems into the smaller components, more effective prioritizing of objectives in a dynamically changing environment, shifting from external to internal gratification, internalization of clinical concepts and demonstrating steady behavioral patterns resulting in the successful outcomes of simulated cases. Conclusion: Multiple exposures to the authentic dynamic and highly interactive simulation cases in the immersive environment result in steady improvement of clinical behaviors. Our future plans include expanding the variety of cases and developing the instruments to objectively measure clinical performances.